Rural Farmers’ Perception of Radio Agripreneurial Programmes in Ogun State, Nigeria - Soyinka, Ademolu Irebami; Biobaku, Mufutau Olanrewaju; Akintunde, Akanni (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025DO - 10.58709/niujss.v11i4.2331, 2025)
Radio intensifies its crucial role in sparking interest and giving rural farmers a deep understanding of agricultural issues, but few existing bodies of research in Nigeria has yet to clearly assess the extent radio agricultural programmes have prioritised issues rural farmers are desirous and the reasons for the transmission of radio agricultural programmes. Hence this study attempted to assess the perception of radio agripreneurial programmes in sparking agripreneurship interests among rural farm settlers in Ogun State, Nigeria. Guided by the Perception Theory, this study adopted a descriptive research design, relying on both quantitative and qualitative data from questionnaires and interviewers’ guide to elicit response from 299 farm operators from Ogun State farm settlements and two producers of agricultural programmes in the State. It found that radio agricultural programmes did not prioritise issues desired by farmers such as funding, marketing, mechanized farming methods and access to agricultural implements, rather it placed emphasis on seedlings and food production. The study recommended that radio agricultural programmes producers embark on extensive research on pertinent agricultural issues that will cater to the agripreneurial needs of the rural farmers which is achievable through engaging experts to handle the production and presentation of agripreneurial programmes on radio. Keywords: Agripreneurship, Agricultural Programmes, Farmers, Perception, Producers, Radio, Rural Farmers